Characterisation of follicular dendritic cells in labial salivary glands of patients with primary Sjogren syndrome: comparison with tonsillar lymphoid follicles. Issue 2 (1st February 1997) - Aziz, Karim Elias; McCluskey, Peter J; Wakefield, Denis
Abstract : OBJECTIVE: To localise and characterise follicular dendritic cells (FDC) present in autoimmune lesions of primary Sjogren syndrome. METHODS: Cryostat sections of labial salivary glands from 15 patients with primary Sjogren syndrome were examined by an indirect immunoperoxidase technique and monoclonal antibodies to a panel of dendritic cell markers. Tonsils from two controls were also examined for the same markers. RESULTS: FDC were localised in the centre of 75% of lymphoid focal structures in labial salivary gland biopsies. FDC in labial salivary glands of patients with primary Sjogren syndrome expressed CD35, CD11c, and CD106 (VCAM-1) in a pattern similar to FDC in tonsils, but they did not express either CD14 or CD11b. This indicates that they may not be of myeloid origin, while FDC in tonsillar lymphoid follicles strongly expressed both CD14 and CD11b. FDC in labial salivary glands of patients also lacked VLA-2α and VLA-3α, which were expressed by FDC in tonsils. CONCLUSIONS: The characteristic phenotype and origin of these cells may be of importance in the immune responses involved in Sjogren syndrome and the retention of infiltrating lymphocytes in the glands.